Development of a Cooperation Framework for Cross-Functional Teams - Friberg, Julia; Johansson, Therese (My University, 2017)
This master’s thesis explores how designers and developers collaborate and communicate in cross-functional teams when developing software within the IT industry. The work includes a social study of the current situation and mapping of the current problem areas, which later served as the base for the development of guidelines on how to best work within cross-functional teams. Later, the result is presented as a collaborative web page containing guidelines that provide an opportunity for others within the field to share their experiences of working in cross-functional teams. The guidelines are then followed by suggestions for further work within this area.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science